Development Of A Phytochemical Based Soap For Topical Management Of Psoriasis - V. Gujar, Sagar; A. Jape, Pratik; T. Kambale, Prathamesh; B. Salke, Somnath; Aher, Sunil J.; Deshpande, Amol; Deokule, Hemant (Journal of Neonatal Surgery, 2025)
The inflammatory condition known as psoriasis results in deformities and unpleasant, scaly, itchy skin. Due to the lack of a viable treatment and associated problems with allopathic drugs, a great deal of research has been done on natural items with anti-psoriatic qualities. The glycerin soap base used in this research article was chosen for its ability to hold onto moisture and mild cleaning properties. This base is completed with potent herbal extracts, including neem, which is praised for its antibacterial and antifungal properties; nutmeg, which is known for its anti-inflammatory and antioxidant properties; turmeric, which is well-known for its anti-inflammatory properties; licorice root, which is prized for its calming and anti-inflammatory properties; and aloe vera powder, which is well-known for its moisturizing and restorative qualities. A herbal anti-psoriatic topical medication delivery system was developed with consideration for the previously given rationale. Through meticulous formulation, we have optimized the concentrations of these components to ensure efficacy while minimizing adverse effects. Our objective is to develop a soap that not only lessens the symptoms of psoriasis but also enhances skin health. This study provides a potential alternative for anyone searching for a gentle yet effective method of managing their psoriasis. Future research efforts will primarily focus on clinical trials to verify the efficacy and safety of this herbal soap formulation, which may result in a breakthrough in the treatment of psoriasis.